Menyuarakan Keadilan Sosial di Tengah Kebisuan: Kajian Teologis Kepemimpinan Kristen berdasarkan Amsal 31:8-9 - Pattinaja, Aska Aprilano (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2025)
In today's reality, there are many injustices that occur and are deliberately silenced. Many Christian leaders miss the opportunity to speak the truth under the pressure of today's challenges. This study shows that Proverbs 31:8-9 serves not only as an ethical guide, but also as a specific call for Christian leaders to advocate for justice at all levels of society. There is a research gap in discussing the theological study of Christian leadership from the perspective of the wisdom literature of Proverbs 31:8-9. Therefore, using the hermeneutic research method of the Wisdom Literature sub-genre, this study highlights three main aspects: first, the moral responsibility of a leader to be a voice for the oppressed; second, the importance of courage in the face of structural injustice; and third, the commitment to uphold truth and protect human rights as a reflection of divine character in building leadership based on social justice. The findings of this study provide theological and practical contributions for Christian leaders who seek to emulate biblical values in leading with a just conscience.